Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/jid.2010.266
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cutaneous Squamous Cell Carcinoma Microenvironment Is Characterized by Increased Lymphatic Density and Enhanced Expression of Macrophage-Derived VEGF-C

Abstract: Metastases from primary cutaneous squamous cell carcinoma (SCC) account for the majority of the ∼10,000 non-melanoma skin cancer deaths in the United States annually. We studied lymphangiogenesis in human SCC because of the potential link to metastasis. SCC samples were stained for lymphatic endothelial vessel marker LYVE-1 and positive cells were counted and compared with cells in normal skin. Gene set enrichment analysis and reverse transcription (RT)-PCR were performed on SCC, on adjacent non-tumor-bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 31 publications
1
100
0
2
Order By: Relevance
“…Activation of angiogenesis facilitates tumor growth by provision of oxygen and nutrients, whereas activation of lymphangiogenesis facilitates tumor dissemination (1). Angiogenesis and lymphangiogenesis are induced in human cutaneous SCCs (20,21). This is accompanied by increased expression of genes associated with lymphangiogenesis, such as VEGF-C, Nrp-2, and VEGFR-3, in peritumoral skin (20).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of angiogenesis facilitates tumor growth by provision of oxygen and nutrients, whereas activation of lymphangiogenesis facilitates tumor dissemination (1). Angiogenesis and lymphangiogenesis are induced in human cutaneous SCCs (20,21). This is accompanied by increased expression of genes associated with lymphangiogenesis, such as VEGF-C, Nrp-2, and VEGFR-3, in peritumoral skin (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of the tumor microenvironment also has been emphasized by description of tumor-associated macrophages that may function as a second source of lymphangiogenic factors. 68,69 In the majority of clinical studies, a significant correlation has been observed between lymphatic vessel density and lymph node and organ metastasis (see meta-analyses in refs 70 --72). This has led to the concept that the denser the lymphatic vasculature is within or close to the tumor, the more potential entry sites the tumor cells have to vessels that could be used as highways for metastatic spread.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
“…Tumour associated macrophages (TAMs) in turn express growth factors and matrix-proteases, promote angiogenesis and suppress adaptive immunity even while helping the host to inhibit tumour growth and destroy neoplastic cells (Mantovani, Bottazzi et al 1992;Sica, Allavena et al 2008). For instance, VEGF-C produced by TAMs in cSCC leads to lymphangiogenesis which then results in increased lymphatic vessel density (Belkin, Mitsui et al 2011), which in turn is linked to metastatic progression (Belkin, Mitsui et al 2011;Moussai, Mitsui et al 2011).…”
Section: Inflammatory Crosstalk In the Microenvironment Of Tumour Stromamentioning
confidence: 99%